Rapid Direct Disc Diffusion Tests (RDDDT) Direct From Blood Cultures (BSI) with Gram-negative Bacilli (GNB) Coupled with Prompt Intervention is an Effective and Safe Antibiotics Stewardship Strategy. (4th October 2017) - Hun, Wint Thu; Sirajuddin, Sara; Saito, Hiroki; Evans, Kaye D; Bittencourt, Cassiana; Peterson, Ellena M; Park, Steven; Thrupp, Lauri
Abstract: Background: Early diagnosis of BSI and appropriate antimicrobials are crucial; additionally avoidance of overly broad antibiotics is important to curb the development of resistance. Rapid molecular approaches are costly and have spectrum limitations. In our prior pilot study simple phenotypic RDDDT provided accurate susceptibility data for GNB over 24 hours earlier than conventional methods. This follow up pilot study evaluated RDDDT plus prompt stewardship intervention to decrease the time to optimal antimicrobial therapy. Methods: GNB positive blood cultures (BACTEC) were inoculated by expressed swab to MH agar plates. 12 antibiotic discs were applied. After at least 8 hr incubation, results in conjunction with MALDI-TOF speciation, were reported to EMR at 9am or 3pm. After review the ID Fellow contacted the primary MD to escalate, deescalate, or continue current antibiotics. Results of the RDDDT were compared with routine VITEK and assessed as complete agreement (CA) or as very major (VM), major (M), minor (MI) discrepancies. Times to susceptibility, RDDDT based antibiotic optimization, and VITEK reports were assessed. Time to VITEK based optimization was obtained from the prior baseline pilot study. Results: 164 patients with GNB were evaluated. 1688 individual RDDDT readings, including 297 ESBL and 66 CRE were compared with VITEK. RDDDT had 85% CA and 0.4% VM, 2.3% M, 13% MI discrepancies. The median time from BC positivity to RDDDT report was 17.5 hours vs. 46 hours for VITEK. Of 164 patients, 162 were assessed clinically. Of those, 72 (44%) required antibiotic change with median time to optimization 21 hours based on RDDDT vs. 71 hours based on prior baseline VITEK. Conclusion: RDDDT coupled with prompt stewardship intervention provided a safe and reliable strategy to improve time to antibiotic optimization with savings of ~2 days compared with standard VITEK reporting. Furthermore, RDDDT is simple and applicable worldwide, especially in resource limited areas. Disclosures: All authors: No reported disclosures.